Electromechanical properties and structure of stretchable and highly conductive polymer hydrogels. Issue 1 (11th December 2018) - An, YingJun; Iwashita, Kana; Okuzaki, Hidenori
Abstract: The stretchable and highly conductive polymer (S-CP) hydrogels were fabricated by casting a water solution of poly(3, 4-ethylenedioxythiophene) doped with poly(4-styenesulfonate) (PEDOT:PSS) and polyacrylamide (PAAm) and subsequent swelling in water. The mechanical properties, electrical conductivity, and structure of the S-CP gels with different weight ratios of the PAAm (WPAAm ) were investigated by means of the tensile test, four-probe method, scanning electron microscopy (SEM), and electron probe micro analysis (EPMA). It was found that the S-CP gels were composed of soft and stretchable PAAm-rich porous network surrounded by the PEDOT:PSS-rich conductive network layers, exhibiting excellent electrical conductivity (17 S cm −1 ) and fracture strain (110%) though it contained 92% of water at WPAAm = 64 wt%. Furthermore, the electrical conductivity of the S-CP gel was improved by stretching up to 75% due to the orientation of the PEDOT:PSS-rich conductive network layers so as to keep the resistance constant, which had potential applications to smart electrodes for soft sensors and actuators in a new field of wet electronics using hydrogels, so called 'gelectronics'.